2019
DOI: 10.1016/j.tcs.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Parameterized and approximation complexity of Partial VC Dimension

Abstract: We introduce the problem Partial VC Dimension that asks, given a hypergraph H = (X, E) and integers k and ℓ, whether one can select a set C ⊆ X of k vertices of H such that the set {e ∩ C, e ∈ E} of distinct hyperedge-intersections with C has size at least ℓ. The sets e ∩ C define equivalence classes over E. Partial VC Dimension is a generalization of VC Dimension, which corresponds to the case ℓ = 2 k , and of Distinguishing Transversal, which corresponds to the case ℓ = |E| (the latter is also known as Test … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…We first study d-Tracking Set, which is a restricted version of Tracking Set System where the size of subsets in the family is restricted to d. We show d-Tracking Set to be NP-hard by showing a correlation with the problems Identifying Vertex Cover and Packing [7], [8]. We then give a compression Tracking Set System is known to be related to Test Cover [10]. Test Cover requires finding a subfamily of sets in a set system, that can help identify each element in the universe uniquely by inclusion.…”
Section: Tracking Set Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…We first study d-Tracking Set, which is a restricted version of Tracking Set System where the size of subsets in the family is restricted to d. We show d-Tracking Set to be NP-hard by showing a correlation with the problems Identifying Vertex Cover and Packing [7], [8]. We then give a compression Tracking Set System is known to be related to Test Cover [10]. Test Cover requires finding a subfamily of sets in a set system, that can help identify each element in the universe uniquely by inclusion.…”
Section: Tracking Set Systemmentioning
confidence: 99%
“…Some results by Crowston et al [11] on Test Cover have been summarized in the following theorem. Test Cover is known to be a dual of Tracking Set System [10], as explained in the following lemmas. Gutin et al [24] have shown that there does not exist a polynomial kernel for Test Cover when parameterized by solution size, under standard complexity theory assumptions.…”
Section: Tracking Set For Set Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…SUPPORT VECTOR MACHINE LEARNING FOR ROLLER BEARING FAULT DIAGNOSIS PROCESSA. SUPPORT VECTOR MACHIMECorinna Cortes and Vapnik developed the currently used SVM technique to minimize the VC dimension[27][28][29][30][31]. The hyperplane, which separates data (…”
mentioning
confidence: 99%